The critical nexus between bioenergy and land use - Baral, H.; Shin, S.; Murdiyarso, D. (Center for Global Sustainability, Centre for International Forestry Research-World Agroforestry (CIFOR-ICRAF), and IPB University, 2023)
A new policy brief from leading experts at the Centre for International Forestry Research-World Agroforestry (CIFOR-ICRAF) and IPB University, as a part of the Center for Global Sustainability’s (CGS) Indonesia Program new guest policy brief series, provides an overview of the crucial interconnection between bioenergy and land use, focusing specifically on the production and employment of biomass for bioenergy and biomaterial. This guest analysis evaluates four case studies to understand sustainable biomass management methodologies.